A nationwide study of patients hospitalised for poisoning in Korea based on Korea National Hospital Discharge In-Depth Injury Survey data from 2005 to 2009. Issue 11 (9th November 2015) - Kim, Kyunghee; Choi, Jae Wook; Park, Miso; Kim, Min Soo; Lee, Eun Sun
Abstract : Objectives: In light of the need to develop an integrated database on poisoning incidents in Korea, this study seeks to determine the characteristics of poisoning incidents in Korea by age, gender, location of incident, causative substance and patient prognosis. Data sources: The Korea National Hospital Discharge In-Depth Injury Survey results (2005–2009) from the Korea Centers for Disease Control and Prevention were used. Participants: 3826 participants in the survey who had been hospitalised for poisoning incidents. Results: The poisoning hospitalisation rate per 100 000 population was higher in women (1.735) than in men (1.372) and increased with age: the rate was 0.458 among individuals aged ≤9 years, 0.481 among those aged 10–19 years, 1.584 among those aged 20–64 years and 4.053 among those aged ≥65 years. The intentional poisoning hospitalisation rate differed by gender and age group. Women aged ≤19 years and 20–64 years showed a higher hospitalisation rate than men, while men aged ≥65 years showed a higher hospitalisation rate than women in the same age group. The most common poisoning substance was pesticides (33.6%), while antiepileptic, sedative-hypnotic and antiparkinsonism drugs and psychotropic drugs, not elsewhere classified were also very common. Poisoning in those aged ≤9 years usually involved other drugs, while pesticides were the most common substances in those aged 20–64 years and ≥65 years. Conclusions: This study analysed poisoning incidents in Korea from 2005 to 2009, by age and gender, causative substance, and characteristics. The results of this study may serve as evidence for new strategies in Korea to prevent poisoning.